Nomenclatural notes on Euphrasia coerulea Tausch (Orobanchaceae) - Szeląg, Zbigniew (Phytotaxa, 2014)
Euphrasia coerulea Tausch (1834a: 445) was described based on specimens from the Isergebirge (now Jizerské hory Mountains in the Czech Republic) in the Western Sudetes. The species occurs in Central Europe, in the Hercynian and Carpathian provinces (Smejkal 1963: distribution map). The name E. coerulea was validated by Tausch (1834a: 445) by means of the shortest possible diagnosis: ‘ganz blaue Blumen’ as opposed to the white flowers characterizing E. officinalis var. alpestris Günther et al. (1824: 164) with which Tausch compared his new species. Junger and Engler (Junger 1867), followed by Kerner (1881: 44), Wettstein (1894: 95, 1896: 115), and Smejkal (1963: 28), considered E. coerulea as a nomen nudum, but acknowledged that it was published in Synopsis Florae Germanicae et Helveticae (Koch 1837: 546). They illegitimately renamed the species E. uechtritziana Junger & Engler (Junger 1867: 141), with “E. coerulea Tausch (pl. sel. Boh.) Koch’s Syn. etc. (1837)” cited in synonymy.